EDUKASI LITERASI KEUANGAN DALAM COMMUNITY SERVICE SEBAGAI STRATEGI PENINGKATAN AKSES MOBILITY BERKREDIT - Ningsi, Etty Harya; Yanti, Tri Auri; Nurhadi, A'an (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2025)
Low financial literacy remains a major barrier to public access to credit-based mobility services, particularly among lower-middle-income communities. This community service initiative was carried out in response to the need for applicable and contextual financial education aimed at enhancing individuals' ability to make informed financial decisions. The activities were implemented using a participatory educational approach, involving training sessions, financial management simulations, and focused group discussions within the UNISZA student community located at UMN Al Wasliyah. The results indicate an increase in participants' understanding of key financial literacy concepts such as budgeting, credit risk assessment, and vehicle financing strategies. In addition, participants exhibited greater enthusiasm and confidence in accessing mobility credit schemes. These findings suggest that an educational approach in community service can serve as an effective strategy to bridge the gap in access to mobility credit. In conclusion, financial literacy instilled through this community engagement program has the potential to empower communities to improve their quality of life through more inclusive and sustainable mobility access.